Louisiana Creole Peoplehood : Afro-Indigeneity and Community - Jolivette, Andrew, 1975-; Barthe, Darryl, Jr; Gomez, Rain C. (Book collections on Project MUSE., 2022)
"Louisiana Creole Peoplehood is a multivocal and collectively structured volume that intervenes against the erasure of Creole Indigeneity while foregrounding Black/Indian cultural sustainability. Divided into sections focused on sacred history, land, language, and cultural practices, contributors engage themes as varied as foodways, queer identity, health, historical trauma, gender, language revitalization, and diaspora. Offering up an understanding of Creole community identity formation and practice at the intersections of both African and Indigenous diasporas, the book combines scholarly analysis with interviews, essays, and autobiographic contributions-including integrating the perspectives of community members in response essays. Louisiana Creole Peoplehood explores the vital ways Afro-Indigenous peoples are asserting their right to exist amidst the backdrops of settler colonialism, anti-Black racism while promoting communal dialogue and community reciprocity"--